Passivation Layers in Lithium and Sodium Batteries: Potential Profiles, Stabilities, and Voltage Drops. (4th May 2021) - Xiao, Chuanlian; Usiskin, Robert; Maier, Joachim
Abstract: The profiles of the decisive thermodynamic potentials in a battery are analyzed with emphasis on the solid electrolyte interphase (SEI) passivation layers that form. Consequences for growth and chemical stability are discussed. The extreme cases of an artificial SEI and a thermodynamically fully defined in situ SEI are distinguished. The analysis also includes the open‐circuit voltage drop over the combination SEI/electrolyte. The treatment is rigorous for the assumed simplified conditions (constant transport coefficients, pseudo‐1D geometry, and absence of space charge zones and structural complications). In the last section, more realistic situations are addressed on a less quantitative level. The results can also be applied to fuel cells or electrolyzers. Abstract : Profiles of the relevant thermodynamic potentials, growth behaviour, and voltage drops are treated predominantly for the two extreme cases shown in the figure. Top: native, equilibrium passivation layer. Bottom: artificial, inert solid electrolyte layer. (In the first case the stationary chemical potential drops are fixed and the thicknesses respond, while this is opposite in the second case.)